Pien Tze Huang Inhibites Colorectal Cancer Cell via Regulating Hedgehog Signaling Pathway in Vivo and in Vitro - Qunchuan ZHUANG; Minghe LIN; Lihui WEI; Jun PENG; Jiumao LIN (康复学报)
Objective:To explore the effect and underlying mechanism of Pien Tze Huang (PZH) inhibiting colorectal cancer cell via regulating Hedgehog signaling pathway in vivo and in vitro.Methods:Human colorectal cancer cells (HT-29) were treated with different concentrations (0, 250, 500, 1 000 μg/mL) of PZH. Cell viability and cell survival were calculated by MTT assay and colony formation assay. RT-PCR was used to determine the expression of PCNA, Bcl-XL, Bax, Survivin and the core genes of Hedgehog signaling pathway, including Shh, Ptch, Smo and Gli1. Mice were given intragastric administration of 234 mg/ (kg·d) dose of PZH or saline daily, 5 days a week, and were taken materials on the 16th day in a nude mouse xenograft study. Tumor samples were analysed by immunohistochemstry for Ki-67, Shh, Ptch, Smo, Gli1.Results:HT-29 cells were inhibited by PZH in a dose dependent manner measured by MTT assay, colony formation assay and in vivo nude mouse xenograft study. The induction of apoptosis as along with the inhibition of cell proliferation was confirmed by down-regulating the expression of Ki-67, PCNA, Bcl-XL and Survivin, and up-regulating Bax expression. The expression of Shh, Ptch, Smo and Gli1 was significantly suppressed by PZH treatment examined by RT-PCR and immunohistochemstry analysis.Conclusion:In vivo and in vitro study, it suggested that promotion of cancer cell apoptosis and inhibition of proliferation via suppression of Hedgehog signaling pathway might be one of the mechanisms by which PZH treats colorectal cancer.